PERLINDUNGAN HUKUM TERHADAP HAK PEMULIA TANAMAN ATAS PRODUK TANAMAN HIBRIDA SEBAGAI BAGIAN DARI HAK KEBENDAAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The law protection towards plant breeder upon plant hybird product aims to shove the spirit and creativity in plant breeder field, with the result that the society needs of high yielding variety can be fulfilled. IPR related to the right of goods which its proprietary can be shifted. IPR as the incorporeal moving things which immaterially or intangible refers that this right of goods gives pleasure or can be a guarantee, either in a pawning regulates in Civil Law book or fiduciary regulates in Law Number 42 Year 1999 concerning Fiduciary Security. According to Law Number 29 Year 2000 concerning The Law Varity Protection, there are 3 (three) form of law protection that can be achieved by the plant hybrid breeder. First, the temporary law protection is given until the right has given since the plea submission is completed and accepted by the Head Office of Plant Variety Protection. Second, if the inquiry result of that variety is appropriate to the law regulation, the right would be given through the approval of the Plant Variety Protection conferral. It is given in the form of certificate. Third, having the certificate of Plant Variety Protection right shows that the protection of plant variety includes in Intellectual Property Right. IPR is incorporeal moving things related to the property rights adhered to its proprietor. The consequence is the proprietor of the plant variety protection has the right to make use of the production of its plants or to give an agreement to other party or corporation to make use of it. The research result also shows that the obstacle in the implementation of the plant breeder protection comprises normative, political, economical, and psychological obstacles. IPR as incorporeal moving things contain substantive characteristic which can be in care of material guarantee. Therefore, the material guarantee can be in care of IPR is fiduciary guarantee and pawnin